Association of pediatric obesity and asthma, pulmonary physiology, metabolic dysregulation, and atopy; and the role of weight management. Issue 5 (3rd September 2019) - De, Aliva; Rastogi, Deepa
ABSTRACT: Introduction : Obesity affects about 40% of US adults and 18% of children. Its impact on the pulmonary system is best described for asthma. Areas covered : We reviewed the literature on PubMed and Google Scholar databases and summarize the effect of obesity, its associated metabolic dysregulation and altered systemic immune responses, and that of weight gain and loss on pulmonary mechanics, asthma inception, and disease burden. We include a distinct approach for diagnosing and managing the disease, including pulmonary function deficits inherent to obesity-related asthma, in light of its poor response to current asthma medications. Expert opinion : Given the projected increase in obesity, obesity-related asthma needs to be addressed now. Research on the contribution of metabolic abnormalities and systemic immune responses, intricately linked with truncal adiposity, and that of lack of atopy, to asthma disease burden, and pulmonary function deficits among obese children is fairly consistent. Since current asthma medications are more effective for atopic asthma, investigation for atopy will guide management by distinguishing asthma responsive to current medications from the non-responsive disease. Future research is needed to elucidate mechanisms by which obesity-mediated metabolic abnormalities and immune responses cause medication non-responsive asthma, which will inform repurposing of medications and drug discovery.